Asia Pacific Consensus Statements on Crohn's disease. Part 1: Definition, diagnosis, and epidemiology: (Asia Pacific Crohn's Disease Consensus—Part 1). Issue 1 (January 2016) - Ooi, Choon Jin; Makharia, Govind K; Hilmi, Ida; Gibson, Peter R; Fock, Kwong Ming; Ahuja, Vineet; Ling, Khoon Lin; Lim, Wee Chian; Thia, Kelvin T; Wei, Shu‐chen; Leung, Wai Keung; Koh, Poh Koon; et al.
Abstract: Inflammatory bowel disease (IBD) was previously thought to be rare in Asia, but emerging data indicate rising incidence and prevalence of IBD in the region. The Asia Pacific Working Group on Inflammatory Bowel Disease was established in Cebu, Philippines, at the Asia Pacific Digestive Week conference in 2006 under the auspices of the Asian Pacific Association of Gastroenterology with the goal of developing best management practices, coordinating research, and raising awareness of IBD in the region. The consensus group previously published recommendations for the diagnosis and management of ulcerative colitis with specific relevance to the Asia‐Pacific region. The present consensus statements were developed following a similar process to address the epidemiology, diagnosis, and management of Crohn's disease. The goals of these statements are to pool the pertinent literature specifically highlighting relevant data and conditions in the Asia‐Pacific region relating to the economy, health systems, background infectious diseases, differential diagnoses, and treatment availability. It does not intend to be all comprehensive and future revisions are likely to be required in this ever‐changing field.